Implementation of the Directorate General of Treasury’s Electronic-Office Online Application at the Makassar State Treasury Service Office - Muh. Nasrullah; Muhammad Luthfi Siraj; Didin; Siti Syarifah Wafikah Wardah (Technium Social Sciences Journal, 2023)
This study aims to find out and analyze the implementation of the Directorate General of Treasury application at the Makassar State Treasury Service Office from a communication perspective. This research method is a qualitative type with a policy approach to analyze government policies through data collection techniques of interviews, observation and documentation as well as analytical techniques used qualitative interactive models with four paths, namely data reduction, data presentation and drawing conclusions. The results showed that the implementation of the e-DJPb Online Application at the Makassar State Treasury Service Office was considered to be implemented quite effectively and efficiently. This is marked by the process of implementing inter-agency communication from the Directorate General of Taxes from the central to the regions which has been informed in stages regarding the regulations governing the implementation of the e-DJPb application which has been transformed into an online-based service. Apart from that the level of communication by the Makassar state treasury service office has also provided clear and transparent information to the public through regular outreach activities and this information has also been conveyed by local officials to the communities it serves. With the distribution of information carried out by local employees, it makes it easier for the community to do tax administration online and creates paper and cost efficiency so that the local government no longer spends the budget for administrative purposes that have been integrated into the online system.